Gestión financiera adoptada por las empresas dedicadas al servicio de mantenimiento y limpieza: caso ASOSERLIMLOSRI S.A. de la ciudad de Babahoyo periodo 2018-2021. - Coronel Bacacela, Andrea Beatriz (2022)
ASOSERLIMLOSRI SA, is a company that provides cleaning and maintenance services in the province of Los Ríos, the main objective is to generate an efficient service to the real estate of each of the institutions, whether they are public or private in the peripheral, with more than Five years of experience, it is constantly evolving and adapting, always at the forefront in acquiring up-to- date tools and fully trained personnel. The objective of this case study is to make known the financial structure on which the company in question sits, the analysis of the structure managed by historical flows, will allow us to demonstrate the movement that has been generated over time, This through the use of the financial tool that we know as vertical analysis, on the other hand, we will also carry out a horizontal analysis between consecutive periods, which will lead us to know how much each of the accounting accounts has been growing over time. The methodology used corresponds to the inductive model because an analysis and description of data will be generated from the financial statements to find declines and establish corrective measures and concrete conclusions.